The Special Theory of Relativity Presented in Physics Textbooks is Incorrect - Alexander Alexandrovich Antonov (New Approaches in Engineering Research Vol. 13, 2021)
It is shown that the entire practice of using Ohm’s law in the theory of linear AC circuits is a theoretical and experimental evidence of physical reality of imaginary numbers. And therefore, the version of the special theory of relativity (STR) set forth in all physics textbooks, denying physical reality of imaginary numbers through the use of the principle of light speed non-exceedance, is incorrect.